Fault reconstruction method of high redundancy satellite power distribution unit - Zeyu Ye; Jingyuan Yin; Tongshuo Zhang; Sha Zheng; Qingpeng Zeng; Tongzhen Wei (IET Power Electronics, 2023)
Abstract Satellite electrical power supply system requires higher redundancy and reliability. The failure of the secondary power supply of the power distribution unit will directly lead to the unavailability of the load. The matrix switch can connect multiple secondary power supplies to multiple loads to improve the fault tolerance of the distribution unit. As the number of redundant switches increases, the process of fault reconstruction becomes more complex. In this paper, a matrix switch fault reconstruction method based on 0–1 integer programming is proposed. This method can reconstruct the matrix switch for different fault modes to meet the electrical power supply and protection requirements of the load. Compared with the general fault countermeasure, this method has independent decision‐making ability, can be expanded by modifying a few parameters, and can be integrated into the management of the whole satellite power supply system. A 500‐W satellite power supply system experimental platform was built, and a matrix distribution switch unit prototype meeting the requirements of integration and low volume was manufactured. The experimental results verify the effectiveness of the reconstruction strategy when dealing with multiple faults in different locations.